Case Report: A wrong turn: malpositioned pacemaker leads reveal undiagnosed PAPVD after emergency implantation - Yana, Yakhimovich; Marat, Aripov (Frontiers in Cardiovascular Medicine, 2025)
Malposition of pacemaker leads into the left heart is a rare but clinically significant complication that can lead to systemic thromboembolism. We report the case of a 78-year-old woman who underwent emergency pacemaker implantation due to sinus node dysfunction. Post-procedural imaging incidentally revealed lead malposition into the left heart. Further investigation using transthoracic and transesophageal echocardiography, along with computer tomography, identified a sinus venosus defect and partial anomalous pulmonary venous drainage. Moreover, malposition of the pacemaker leads was confirmed. Given the patient's age, frailty, and absence of thromboembolic events or significant symptoms, a conservative approach was chosen, and lifelong anticoagulation with warfarin was initiated. Surgical intervention and lead extraction were deferred due to high procedural risk. The patient remained clinically stable with preserved pacemaker function and no complications during follow-up. This case underscores the importance of imaging in detecting anomalies associated with pacemaker lead malposition. Management should be individualized, balancing procedural risk against the potential for thromboembolism.